Apigenin ameliorates CCl4-induced hepatic fibrosis by inhibiting hepatic stellate cell activation via PI3K/AKT/GSK3β pathway in mice - Tao Sun; Bao-Ying Wang; Xiao-Ying Li; Xiu-Zhi Zhang; Yan-Fei Lei; Shan-Fa Yu; Ning-Ning Li (Asian Pacific Journal of Tropical Biomedicine)
Objective: To investigate the effect of apigenin on carbon tetrachloride (CCl4)-induced liver fibrosis and elucidate the underlying mechanisms. Methods: A mouse model of CCl4-induced liver fibrosis was used to evaluate the effects of apigenin. Liver function was assessed using biochemical tests, and inflammation-associated markers, including interleukin-1 beta (IL-1β), IL-6, IL-10, and tumor necrosis factor- alpha (TNF-α), were determined by enzyme-linked immunosorbent assay (ELISA). H&E staining, Sirius Red staining, and collagen immunohistochemistry were also conducted. In addition, antioxidant enzyme activity and the underlying mechanisms of hepatoprotective effects of apigenin were examined. Results: CCl4 administration induced hepatic stellate cell activation and liver fibrogenesis in mice. Apigenin treatment markedly decreased liver injury markers, inflammation, oxidative stress, and collagen deposition, mitigating CCl4-induced liver fibrosis. Furthermore, it significantly suppressed the activation of the phosphoinositide 3-kinase/protein kinase B/glycogen synthase kinase 3 beta (PI3K/AKT/GSK3β) pathway by reducing the ratios of p-PI3K/PI3K, p-AKT/AKT, and p-GSK3β/GSK3β in liver tissue. Conclusions: Apigenin ameliorates CCl4-induced liver fibrosis in mice, likely through the inhibition of the PI3K/AKT/GSK3β signaling pathway. These findings suggest that apigenin may have therapeutic potential for treating liver fibrosis.